Underlying Implicating factors of U.S. War on Terror and its Unintended Consequences for Pakistan - Asifa Jahangir (Journal of Political Studies, 2019)
Pakistan‟s reactive foreign policy attitudes and actions negate (or seem contradictory to) the core principle of realist paradigm, which says that intentions may vary independently without having any influential peer-pressure. Holistically, the critical analysis of Pakistan‟s foreign policy history exhibits that this country always chooses to pursue a reactive policy rather than proactive one. The best and recent example is Pakistan‟s dealing with Afghanistan problem since 9/11. This study uses archival evidence of long-simmering tensions about the continuing Afghanistan War and its unexpected consequences of Pakistan‟s policy decision to examine hypotheses derived from Barry Buzan‟s Regional Security Complex Theory. This paper aims to make the following inquiries: (1) how did Pakistan react in the response to U.S. invasion of Afghanistan and its War on Terror? (2) What have been the factors implicating Pakistan in Afghanistan War? (3) Why has Pakistan been failed in designing a proactive policy to prevent the challenges surfaced from enduring Afghan conflict and pose the serious threats to its security? (4) What are the unintended consequences of Pakistan‟s reactionary policy towards Afghanistan and in which direction have these outcomes guided Pakistan towards? While foreseeing the deteriorating situation in Afghanistan and its spillover effect on region, this paper will provide Pakistan‟s proactive strategies in the form of National Action Plan and CPEC so as to overcome such possible effects in future over the internal security situation and economic condition of the country.